THE INFLUENCE OF SMO IN UKRAINE ON GDP AND INFLATION IN THE EU WITH REFERENCE TO SERBIA - Zelenović, Prof. dr Vera; Malenković, Nebojša; Zelenović, Jelena (Poslovna ekonomija, 2023)
SMO in Ukraine and the imposed sanctions have their own dangerous economic side effects: a) they seriously affect the existing level of GDP, both in Europe and in the world; b) Inflationary pressure, which was already elevated after the end of the Covid pandemic, began to increase uncontrollably, with varying intensity. Serbia is also not spared from the negative effects of SMO on its economy. Purpose: The war conflict in Ukraine showed that it is not possible to limit the economic (and not only them) consequences, to a certain territory. All this indicates that the global economic connection is great, and that the negative effects of the crisis are reflected on the economic community as a whole. Methodology: In the paper, using the method of content analysis, data available from primary sources. For the research in Serbia, official data from the NBS website were used, when it comes to the movement of GDP, the growth of consumer prices, as a key indicator for measuring inflation, and the movement of nominal wages expressed in euros. For the purposes of the research, an appropriate statistical method, regression, was used.The results of the research indicate a trend of GDP reduction under the influence of SMO and sanctions, both in the world and in Serbia. Inflationary pressure is getting stronger, continuously in all presented data that are the subject of research. The nominal growth of wages in Serbia was shown to be a consequence of inflationary pressure.The limits that exist in relation to this research are the existence of different scenarios for ending this crisis, which implies different conclusions about the measures that should be taken to mitigate it, given that the situation changes on a daily basis. Suggestions for future research are given in the conclusion.
Keywords: European Union, SMO in Ukraine, sanctions, crisis, GDP, inflation